Penerapan Manajemen Risiko Pada Badan Usaha Milik Desa (BUMDesa) Dhana Adhyata di Desa Jehem Kecamatan Tembuku Kabupaten Bangli - Satyarini, Ni Putu Kartika; Sudiana, I Wayan; Putra, I Putu Deddy Samtika (Hita Akuntansi dan Keuangan, 2025)
Credit is one of the main activities carrieds out bys BUM Desa to provide financial support to village communities. Bad credit at BUM Desa refers to a situation where the borrower cannot fulfill his obligations in paying credit installments according to the agreed agreement. The aim ofs sthis research is to analyze and describe how risk management is implemented in the Dhana Adhyata Village-Owned Enterprise (BUM Desa) in Jehem Village, Tembuku District, Bangli Regency. The subjects in this research were the Director, Secretary and Treasurer of Bumdes Dhana Adhyata who acted as informants. The results ofs the research show that through the risk management method BUM Desa negotiates with customers by rescheduling credit payments, reviewing the contents of the credit agreement and making collections if customers still do not make payments after negotiations involving Kelian Dinas, Bimas, Babimsa and BUM Desa Supervisors